1996
DOI: 10.1097/00007890-199611150-00011
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fatty Donor Liver Is Associated With Diminished Early Patient and Graft Survival

Abstract: It is well known that implantation of donor livers with severe fatty infiltration (>60%) is frequently associated with early hepatic dysfunction and an increased incidence of primary nonfunction after liver transplantation. The outcome of donor livers with less fatty infiltration has not been well defined. We, therefore, studied the outcome of 59 liver transplantations in which donor livers with up to 30% fat were used. Patient outcome was compared to a time-matched control group of 57 patients. The two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
223
1
11

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(248 citation statements)
references
References 17 publications
13
223
1
11
Order By: Relevance
“…†During ICU stay. 15,16 Conversely, the results of the ELTR clearly show that donor age over 65 years affects 1-and 5-year graft survival rate (73% and 55%, respectively). According to the last report of the ELTR, the incidence of primary nonfunction or severe graft dysfunction has remained the same during recent years.…”
Section: Discussionmentioning
confidence: 97%
“…†During ICU stay. 15,16 Conversely, the results of the ELTR clearly show that donor age over 65 years affects 1-and 5-year graft survival rate (73% and 55%, respectively). According to the last report of the ELTR, the incidence of primary nonfunction or severe graft dysfunction has remained the same during recent years.…”
Section: Discussionmentioning
confidence: 97%
“…15,[19][20][21][22] It is believed that these factors, usually classified as immunologic and nonimmunologic, also play a role in the transplantation of other organs. 3,4 Some studies have found that race is not a critical factor in liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Brooks et al, 21 in a study of the effect of donor and recipient gender on liver transplantation, found that female recipients had a 70% incidence of early rejection within six months after liver transplant compared with male recipients (60%; P Ͻ .039). They also found a decreased graft survival rate in male recipients of female livers.…”
Section: Discussionmentioning
confidence: 99%
“…37,38,45,46 Clinically, recipients who receive grafts with moderate steatosis (Ͼ25% to 30%) have impaired early graft function in the first 3 days as reflected by a higher peak serum glutamic oxaloacetic transaminase, lower bile output, and increased intraoperative bleeding. Marsman et al 47 transplanted 59 livers with up to 30% fat and compared them to time-matched controls; the fatty liver group had a decreased 4-month graft survival and a decreased 2-year patient survival. In this study, graft survival was decreased if the recipient was more critical pretransplantation.…”
Section: Steatotic Donorsmentioning
confidence: 99%